Vaginismus and Infertility - Rossy Sintya Marthasari; A. Marlinata; Reny I’tishom (Indonesian Andrology and Biomedical Journal, 2020)
Background: Vaginismus described as persistent or reccurent difficulties for woman to allow vaginal entry of a penis, a finger or there is often avoidance and anticipation, fear or experience of pain, along with variable involuntary contraction of pelvic muscle. Reviews: Vaginismus can lead to unconsummated marriage, and also can be hidden caused of infertility. Vaginismus can be categorized as primary (lifelong), patient has never experiences non painful intercourse or secondary (acquired), patient has previously normal but now experience pain. Vaginismus should be considered as part of differential diagnosis in patient who has no satisfaction in sexual intercourse or do not tolerate penetration. Diagnosis is made by making a good history taking. A variety of intervention have been suggested in some case report study. Effective treatment to vaginismus include sex education, psychosexual therapy, systematic desensitization, anxiolytic and Botulinum Toxin (botox). While there are few controlled studies on the management of vaginismus, they are limited and poorly designed. Summary: Goal of treatment is not only to achieve pregnancy but also increase quality of life. Either natural or assisted, vaginismus is still have to be cured. A great teamwork is required to successfull therapy.